2020
DOI: 10.1002/bies.202000078
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Non‐Mechanical Functions of Filamentous and Non‐Filamentous Vimentin

Abstract: Intermediate filaments (IFs) formed by vimentin are less understood than their cytoskeletal partners, microtubules and F-actin, but the unique physical properties of IFs, especially their resistance to large deformations, initially suggest a mechanical function. Indeed, vimentin IFs help regulate cell mechanics and contractility, and in crowded 3D environments they protect the nucleus during cell migration. Recently, a multitude of studies, often using genetic or proteomic screenings show that vimentin has man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 136 publications
1
64
0
Order By: Relevance
“…This especially includes neutrophils ( 26, 27 ) macrophages ( 28 ), and endothelial cells ( 29, 30 ). While early studies have attributed extracellular vimentin to cytoskeletal debris and disruptions in the plasma membrane, it is now clear that it appears in the absence of cell damage ( 31 ). While the functions of cell surface vimentin are still largely mysterious, cell surface vimentin has been shown to act as a biochemical signal between different cell types but also serves as an attachment factor through which multiple types of bacteria and viruses infect cells ( 32, 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This especially includes neutrophils ( 26, 27 ) macrophages ( 28 ), and endothelial cells ( 29, 30 ). While early studies have attributed extracellular vimentin to cytoskeletal debris and disruptions in the plasma membrane, it is now clear that it appears in the absence of cell damage ( 31 ). While the functions of cell surface vimentin are still largely mysterious, cell surface vimentin has been shown to act as a biochemical signal between different cell types but also serves as an attachment factor through which multiple types of bacteria and viruses infect cells ( 32, 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous pathways have been identified for controlled release of vimentin often by inflammatory cells. Extracellular release depends on covalent modifications of vimentin, often by phosphorylation or citrullination ( 30 ). These modifications disassemble cytoskeletal vimentin intermediate filaments and lead to release of vimentin either on the external surface of the same cell or in soluble form or on the surface of exosomes where it can target cells such as epithelial cells ( 58 ) or neurons ( 38, 39 ) that do not express vimentin endogenously.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this surface expression has been linked to malignant tumor progression (Liu et al, 2020). Various posttranslational modifications such as citrullination or phosphorylation are involved in the regulation of vimentin secretion into the extracellular fluid or in mediating surface presentation in different cell types (for review see Patteson et al, 2020). Also, conformational changes have been identified that elucidate mechanisms of membrane integration as a prerequisite for surface location.…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin filaments exist as a cage or mesh structure around the nucleus and are also present in the cytoskeleton in fibrous form as can be seen in Fig. 1(b) [31, 38]. Studies show that vimentin provides structural integrity to the cell [25, 42] and also provides organization for the other cellular parts [43, 44].…”
Section: Modelmentioning
confidence: 99%
“…To do so, we develop a minimal cell motility model incorporating actin, microtubules, and vimentin. The starting point of the model is the hypothesis that vimentin plays a distinct role in mediating forces between the actomyosin cortex and the nucleus [38, 39]. Our model, therefore, contains both an actomyosin cortex and a nucleus, whose interaction via a set of linker springs is strengthened by the presence of vimentin.…”
Section: Introductionmentioning
confidence: 99%